Evidence-Based Updates to Thrombectomy: Targets, New Techniques, and Devices - Yeo, Leonard L. L.; Jing, Mingxue; Bhogal, Pervinder; Tu, Tianming; Gopinathan, Anil; Yang, Cunli; Tan, Benjamin Y. Q.; Arnberg, Fabian; Sia, Ching-Hui; Holmin, Staffan; Andersson, Tommy (Frontiers in Neurology, 2021)
Endovascular thrombectomy (EVT) has been validated in several randomized controlled trials in recent years for its efficacy in the treatment of acute ischemic strokes (AIS) and is now the standard of care according to international guidelines. However, in about 20% of EVT procedures, recanalization is not achieved, and over 50% of patients who undergo EVT still do not have good functional outcome. In this article, we provide an extensive review of the latest evidence and developments in the field of EVT, with particular focus on the factors that improve patient outcomes. These factors include new and adjunctive techniques such as combination of direct aspiration and stent retriever, intra-arterial urokinase or 2b/3a inhibitors, rescue stenting, as well as novel devices including balloon guide catheters and the newer generations of aspiration catheters and stent retrievers. We also examined the latest notion of using first-pass effect (FPE) as the target to achieve during EVT, which has been associated with an improved functional outcome. While the field of EVT has been rapidly evolving, further research is required in specific AIS patient populations such as those with large ischemic core, late presentation beyond 24 h, posterior circulation strokes, and with distal medium vessel occlusion or tandem lesions to better assess its efficacy and safety.